Transverse Cervical Artery for Head and Neck Reconstruction with Free Jejunal Flaps: A Retrospective Study of Computed Tomography Angiography - Fujisawa, Kou; Miyamoto, Shimpei; Saito, Yuki; Suzuki, Sho; Okazaki, Mutsumi (Journal of Reconstructive Microsurgery, 2023)
Background The transverse cervical artery is less commonly used than other external carotid arteries as a recipient vessel. Therefore, we aimed to compare the utility of the transverse cervical artery as a recipient vessel with that of the external carotid artery system for microvascular head and neck reconstruction by quantitative analysis of dynamic-enhanced computed tomography.Methods Fifty-one consecutive patients who underwent free jejunum transfer following total pharyngolaryngectomy between January 2017 and December 2020 were retrospectively reviewed. Ninety-four pairs of the diameters of the transverse cervical artery, superior thyroid artery, and lingual artery, measured via computed tomography angiography, were analyzed. Operative outcomes were compared between the following groups based on the recipient artery: transverse cervical artery (n = 27), superior thyroid artery (n = 17), and other artery (n = 7) groups.Results In the analysis of the computed tomography angiography, nine transverse cervical arteries (9.6%) could not be identified. However, the percentage was significantly lower than the percentage of superior thyroid arteries (20.2%) and lingual arteries (18.1%) (p < 0.01). Among the identified vessels, the transverse cervical arteries (2.09 ± 0.41 mm) and the lingual arteries (1.97 ± 0.40 mm) were significantly larger than the superior thyroid arteries (1.70 ± 0.36 mm) in diameter at the commonly used level (p < 0.01). Multivariate analysis revealed that prior radiation therapy was not an independent factor significantly affecting transverse cervical artery diameter (p = 0.17). Intraoperative anastomotic revision was required in only two cases of the superior thyroid artery.Conclusion The transverse cervical artery can offer a larger caliber and more reliable candidate than the superior thyroid artery for a recipient artery. More liberal use of the transverse cervical artery may improve the safety of microsurgical head and neck reconstruction.
Keywords: transverse cervical artery; computed tomography angiography; head and neck reconstruction; recipient vessel; microvascular anastomosis